ARTIFICIAL INTELLIGENCE AND HUMANITY: RELATIONSHIPS, PROBLEMS, FUTURE - Мормуль, Микола; Щитов, Дмитро; Щитов, Олександр; Романчук, Любов (Modern engineering and innovative technologies, 2024)
The origins, problems and contradictions in the creation and research of artificial intelligence are considered. His roles in cinema and in the future are analyzed. Prospects, paths to directions of development, predictions of scientists and artists rega